2020
DOI: 10.3390/app10196635
|View full text |Cite
|
Sign up to set email alerts
|

Finite Element Analysis (FEA) of Palatal Coverage on Implant Retained Maxillary Overdentures

Abstract: Purpose: The aim of this study was to determine stress levels on supporting structures of implant-retained overdentures as a function of varying degrees of palatal coverage using finite element analysis modeling at different loading angles. Materials and Methods: ABAQUS®-software was used to perform finite element analysis on eight overdenture models with three and four implants and with and without palatal coverage designs. Loads were applied perpendicular and 45º to the implants. Von Mises stress was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Kim et al [35], in a study from 2016, suggested that full palatal coverage is more beneficial for stress distribution, while they preferred the usage of the Hader bar to the milled bar. On the other hand, Fernandez et al [36] found no significant difference under axial loading between the prosthesis with full palatal coverage and without palatal coverage when the bar was added. Under nonaxial loading, the decrease in stress was observed with the bar attachment in all sites, with the exception of the anterior implant site.…”
Section: Discussionmentioning
confidence: 96%
“…Kim et al [35], in a study from 2016, suggested that full palatal coverage is more beneficial for stress distribution, while they preferred the usage of the Hader bar to the milled bar. On the other hand, Fernandez et al [36] found no significant difference under axial loading between the prosthesis with full palatal coverage and without palatal coverage when the bar was added. Under nonaxial loading, the decrease in stress was observed with the bar attachment in all sites, with the exception of the anterior implant site.…”
Section: Discussionmentioning
confidence: 96%
“…The particular parts described in the previous section were assembled in order to obtain the final finite element (FE) model of the overdenture prosthesis. Within the FE framework, linear 4-node elements [14] were assigned to the housing and linear 8-node brick elements [15] with reduced integration [16][17][18][19] to the prosthesis, bar, implants, clips, and edentulous mandible. The FE mesh was created to obtain a regular node pattern.…”
Section: Finite Element Methods Modelmentioning
confidence: 99%